PSYCHOLOGICAL STRATEGIES FOR TEACHER SELF-REGULATION - Saadat, Samadzade; Nazrin, Nasibova; Jeyran, Nazarli; Aysun, İbrahimzada (Health and Society, 2026)
The article examines the manifestations of teachers’ emotional regulation strategies and the psychological functions that influence the selection of different strategies. The study involved 30 teachers from various faculties with diverse academic backgrounds. The study showed that among traditional teachers, emotional suppression predominates in age-related changes, whereas among modern teachers, cognitive appraisal is dominant. It is not academic experience, but rather the demands of the new educational environment that lead teachers to choose more adaptive strategies for managing their emotions. The study shows that as age increases, emotional self-regulation strategies also change. There is a correlation among teachers’ use of cognitive strategy, extraversion, and expressive suppression. According to the typology, the correlation between extraversion and cognitive strategy is more significant than that with expressive suppression (p=0.001). Cognitive reappraisal is positively correlated with extraversion, agreeableness, is positively correlated with extraversion, agreeableness, openness to experience, and conscientiousness, and at the same time, expressive suppression is negatively correlated with neuroticism, extraversion, and openness to experience.